HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN PENGGUNA MOBILE JKN PASIEN RAWAT JALAN DI RSUD OTANAHA TAHUN 2025 - Mohamad Firmansyah Yunus; Moh Ichsan Arifin Antu; Merlin Abd Rahman (PRIMA WIYATA HEALTH, 2025)
Background: Digital transformation in public health services has led to the development of the Mobile JKN application by BPJS Kesehatan, aiming to improve access, efficiency, and quality of outpatient services. However, the implementation still faces challenges related to system reliability, user readiness, and service performance, especially in regional hospitals. Objectives: This study aims to evaluate the relationship between service quality dimensionsm (efficiency, fulfillment, and system availability and patient satisfaction with the use of the Mobile JKN application among outpatients at RSUD Otanaha, Gorontalo. Methods: A quantitative analytic study with a cross-sectional design was conducted in April 2025. A total of 97 respondents were selected using accidental sampling. Data were collected using a structured questionnaire based on the E-S-QUAL model, tested for validity and reliability. Data analysis included descriptive statistics and Spearman correlation using SPSS. Results: The majority of respondents rated the Mobile JKN service as “less good” in efficiency (35.1%) and system availability (41.2%), while 48.5% expressed being “less satisfied” overall. Correlation results showed a strong, positive, and significant relationship between efficiency (r = 0.748), fulfillment (r = 0.624), system availability (r = 0.739), and patient satisfaction (p = 0.000). The results also indicated that elderly patients with lower digital literacy experienced more difficulties using the application. Conclusion: The quality of digital health services, particularly in efficiency and system availability, significantly influences patient satisfaction. Targeted educational interventions and user support are crucial for ensuring equitable access to health technology among vulnerable groups such as the elderly.